1)Doprowadz do najprostrzej postaci. a)-4(-2+6y+5z)-8(9x+8y-7z)+5(3x-6y+9z) b)2/3(3a+6b-12c)+3/5(10a-15b+20c)-0,5(16a+24b-36c) 2)Wyłącz wspolny czynnik poza nawias. a)-6y-9x-3 b)5x-15y-20z c)-6u+12w-9y+6 d)-9+18a-27b+36c e)-x-1,5y-7,5z

1)Doprowadz do najprostrzej postaci. a)-4(-2+6y+5z)-8(9x+8y-7z)+5(3x-6y+9z) b)2/3(3a+6b-12c)+3/5(10a-15b+20c)-0,5(16a+24b-36c) 2)Wyłącz wspolny czynnik poza nawias. a)-6y-9x-3 b)5x-15y-20z c)-6u+12w-9y+6 d)-9+18a-27b+36c e)-x-1,5y-7,5z
Odpowiedź

1) a)-4(-2+6y+5z)-8(9x+8y-7z)+5(3x-6y+9z)= 8-24y-20z-72x-64y+56z+15x-30y+45z= 8-118+81z-57x b)2/3(3a+6b-12c)+3/5(10a-15b+20c)-0,5(16a+24b-36c)= 2a+4b-8c+6a-9b+12c-8a-12b+18c = -17b+30c 2) a)-6y-9x-3= -3(2y+3x+1) b)5x-15y-20z = 5(x-3y-4z) c)-6u+12w-9y+6 = 3(-2u+4w-3y+2) d)-9+18a-27b+36c = 9(-1+2a-3b+4c) e)-x-1,5y-7,5z =-1,5(2/3x+y-5z)

Dodaj swoją odpowiedź